2011
DOI: 10.1073/pnas.1014692108
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state 2 H NMR relaxation illuminates functional dynamics of retinal cofactor in membrane activation of rhodopsin

Abstract: Rhodopsin is a canonical member of the family of G proteincoupled receptors, which transmit signals across cellular membranes and are linked to many drug interventions in humans. Here we show that solid-state 2 H NMR relaxation allows investigation of light-induced changes in local ps-ns time scale motions of retinal bound to rhodopsin. Site-specific 2 H labels were introduced into methyl groups of the retinal ligand that are essential to the activation process. We conducted solid-state 2 H NMR relaxation (spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 54 publications
2
71
0
Order By: Relevance
“…An enhanced insight into the dynamics of rhodopsin activation and interaction with ligand and G protein has been obtained more recently by NMR techniques that show confor- mational flexibility of this receptor and the G protein upon activation (45)(46)(47)(48). Several methods demonstrated that membrane proteins (49), including rhodopsin (50), contain integral ordered water molecules that play important roles in both structure and function.…”
Section: Structures Of Phototransduction and Visual Cycle Componentsmentioning
confidence: 99%
“…An enhanced insight into the dynamics of rhodopsin activation and interaction with ligand and G protein has been obtained more recently by NMR techniques that show confor- mational flexibility of this receptor and the G protein upon activation (45)(46)(47)(48). Several methods demonstrated that membrane proteins (49), including rhodopsin (50), contain integral ordered water molecules that play important roles in both structure and function.…”
Section: Structures Of Phototransduction and Visual Cycle Componentsmentioning
confidence: 99%
“…Previous efforts by several labs have shown that retinal makes state-specific protein-ligand interactions (68)(69)(70)(71)(72). We monitored retinal using three regions of the ligand equivalent to those identified by Brown and coworkers, the orientations of the C5-, C9-, and C13-methyl groups (46,47,(73)(74)(75)(76). In this analysis, the vectors denoted by the three arrows in Fig.…”
Section: Retinalmentioning
confidence: 98%
“…Transitioning to the Meta I state changes the C6-C7 torsion angle to 32° or 57° and makes planes B and C roughly parallel (94). Analysis of 2 H T 1Z and T 1Q relaxation times of the methyl groups as a function of temperature yielded the activation energies (E a ) and order parameters of methyl rotations for the dark, Meta I, and Meta II states (95, 96). The methyl group attached to C5 of the β-ionone ring has the highest E a , which is insensitive to photoactivation (95), consistent with confinement of the ring in the hydrophobic pocket of the protein.…”
Section: Seven-transmembrane-helix Proteinsmentioning
confidence: 99%
“…Analysis of 2 H T 1Z and T 1Q relaxation times of the methyl groups as a function of temperature yielded the activation energies (E a ) and order parameters of methyl rotations for the dark, Meta I, and Meta II states (95, 96). The methyl group attached to C5 of the β-ionone ring has the highest E a , which is insensitive to photoactivation (95), consistent with confinement of the ring in the hydrophobic pocket of the protein. The methyl groups associated with C9 and C13 have energy barriers that change with photoactivation: Retinal isomerization increases the C9 E a but decreases the C13 E a .…”
Section: Seven-transmembrane-helix Proteinsmentioning
confidence: 99%
See 1 more Smart Citation